Analisis Perlindungan Hukum dan Keselamatan Kerja terhadap Tenaga Kesehatan di Indonesia (Neolectura, 2023)
Healthcare professionals, like other employees, are entitled to legal protection under general labor regulations. This implies that their employment relationship with hospitals, which act as their employers, must comply with the applicable laws and regulations. The specific provisions governing this relationship are already established in various legal instruments, including the Law on Health Personnel (Law No. 36 of 2009), the Law on Hospitals (Law No. 44 of 2009), the Law on Health Workers (Law No. 36 of 2014), and other relevant healthcare legislation. This journal article utilized a normative juridical approach, complemented by the collection of secondary data. The decision to use a normative approach was driven by the constraints imposed by the Covid-19 pandemic, which made it difficult to conduct empirical research. The Descriptive Design was chosen as the research design for this study. The data was obtained through an extensive review of existing literature. Qualitative analysis methods were applied to explore the topic of legal protection for healthcare workers.